Home mechanical ventilation in children: The experience of pediatric pulmonology divisions in Istanbul - AY, NADİYE PINAR (My University, 2022)
Background: Prolonged survival of patients with chronic respiratory failure increased the number of patients receiving long-term home ventilation (LTHV). This study aimed to describe the aetiology and patterns of the use of LTHV in Istanbul. Methods: This cross-sectional study included children on home invasive ventilation (IV) and non-invasive ventilation (NIV) from six tertiary hospitals. Data including underlying diagnosis and LTHV were collected from patients' charts. Results: Study included 416 patients. The most common diagnoses were neuromuscular (35.1%) and neurological diseases (25.7%). While 49.5% (n=206) received NIV, 50.5% (n=210) of the patients received IV. The median age at initiation of LTHV was lower in the IV group (10 vs. 41 months, p<0.001). The duration between the indication and start of LTHV was longer in the IV group (30 vs. 8 days, p<0.001). Most of the patients in the NIV group (81.1%) received night-time ventilation while most of the IV group (55.7%) received full ventilation (p<0.001). In addition, 41.9% of the patients in the IV group and 28.6% in the NIV group also received oxygen support (p=0.002). Within last year 59.1% (n=246) of the patients were hospitalized. Risk factors for hospitalizations were IV, full time ventilation, oxygen supplementation, tube feeding and swallowing dysfunction (p 0.002, 0.009, <0.001, <0.001 and <0.001 respectively). Conclusions: This study characterized several previously unknown trends regarding LTHV use in our region. Multidisciplinary follow up of these children is important in order to decrease morbidity and mortality. Optimal nutritional management and surveillance for swallowing problems are vital.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine